EFFECTIVE MANAGEMENT OF FOREIGN ECONOMIC ACTIVITY IS AN IMPORTANT FACTOR IN THE ACCELERATED INTEGRATION OF THE REPUBLIC OF UZBEKISTAN WITH FOREIGN COUNTRIES - Tursunova Muniskhon Rakhimdjanovna (Scholar Express Journals, 2022)
One of our priorities in the economic sphere is to further strengthen the economic ties of our country with foreign countries and increase its international prestige, accelerate the attraction of investments, and further develop the tourism industry by promoting the economic potential of our country abroad. The economic development strategy of Uzbekistan is aimed at creating a diversified and competitive economy, the maximum use of national resources using innovative technologies and new methods of market management. The country’s foreign economic activity, especially in the field of foreign trade, has a direct impact on the standard of living of the population as a result of reforms. The socio-economic reforms carried out in our country are aimed at ensuring long-term sustainable economic growth by increasing production efficiency in all sectors and sectors of the economy. The country has taken a number of positive steps to improve investment policy and attract foreign investment. The bulk of foreign investment is directed to the development of enterprises in the real sector and their technical and technological modernization.
Keywords: Economy; Development; Economic Sphere; Credit